Using the two-source capture-recapture method to estimate the incidence and case ascertainment of congenital rubella syndrome in Australia, 1993-2013 - Nicolee Martin; David Durrheim; Gulam Khandaker; Michelle Butler; Cheryl Jones (World Health Organization Regional Office for the Western Pacific, 2016)
To verify rubella and congenital rubella syndrome (CRS) elimination, countries need to ensure that their surveillance systems are sufficiently sensitive to capture almost all cases. This study aims to estimate the incidence of CRS in Australia and the sensitivity of CRS case ascertainment in the National Notifiable Disease Surveillance System.